A rhetorical grammar : C. Iulius Romanus, Introduction to the Liber de adverbio, as incorporated in Charisius' Ars Grammatica II. 13 - Schenkeveld, Dirk M. (Mnemosyne, Supplements, 2004)
About 280 AD C. Iulius Romanus wrote a large work on Latin grammar. Parts of this work were later incorporated in the Ars grammatica of Flavius Sosipater Charisius. Romanus' Introduction to his list of adverbs is unique because of his approach of the subject. With the help of many rhetorical means he weaves together an intricate argument, which is completely different from the usual treatments of the adverb. This unique character was never noticed previously. The first chapters of this book deal with Charisius and Romanus in general and the Introduction in particular. A new edition with translation and commentary follows, completed by a discussion of the annotations of Cauchius made about 1540 from a manuscript now lost.